ASSOCIATION BETWEEN PHYSICAL ACTIVITY AND BODY COMPOSITION AMONG PHYSIOTHERAPY STUDENTS - Vovkanych, L.S.; Kutseryb, T.M.; Hrynkiv, M.Y.; Muzyka, F.V.; Kras, S.I. (World of Medicine and Biology, 2025)
The purpose of this research was to assess the effects of moderate, non-professional physical activity on the body composition of future physiotherapists. The study involved 102 physiotherapy students (aged 17–18): untrained (M1, F1) and non-professionally trained (M2, F2). Non-professional training lasted up to 5 hours weekly at a moderate activity level. We observed the larger muscle component in group M2 (42.51 %), than in group M1 (40.18 %, p ≤ 0.05), and in F2 (29.56 %) than in F1 (28.33 %, p ≤ 0.05). The fat component was larger in group M1 (18.74%), compared to group M2 (16.30 %, p ≤ 0.05), and in F1 (30.82 %) compared to F2 (27.58 %, p ≤ 0.05). The highest percentage of individuals with normal body mass was found in groups M2 and F2 – 84.2 % and 75.0 %, respectively. The analysis of correlation coefficients demonstrates a general trend of increased fat tissue content (r = 0.789–0.908) and decreased muscle tissue content (r = -0.108–-0.730) with higher BMI. We conclude that engagement in non-professional training induces alterations in both muscle and fat tissue content in the body of physiotherapy students.
Keywords: non-professional training; body mass index; muscle component; fat component